1999
DOI: 10.1016/s0886-3350(99)00107-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in intraocular pressure after clear corneal phacoemulsification: Normal patients versus glaucoma suspect and glaucoma patients

Abstract: Clear corneal phacoemulsification was associated with a statistically significant long-term reduction in IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
137
2
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(162 citation statements)
references
References 11 publications
13
137
2
10
Order By: Relevance
“…Many previous studies including ours 22 showed that CS lowers the IOP for several years; [23][24][25] this is consistent with the results obtained in this study. However, IOP in no eyes that underwent surgery was low enough to cause hypotension maculopathy, and was thus considered to be unrelated to the progression of ERM.…”
Section: Discussionsupporting
confidence: 92%
“…Many previous studies including ours 22 showed that CS lowers the IOP for several years; [23][24][25] this is consistent with the results obtained in this study. However, IOP in no eyes that underwent surgery was low enough to cause hypotension maculopathy, and was thus considered to be unrelated to the progression of ERM.…”
Section: Discussionsupporting
confidence: 92%
“…The drop in IOP observed after 1 month following cataract surgery was in agreement with previous investigations in which IOP has been reported to decrease post-operatively in the mid-to long-term. [1][2][3][4] A post-operative reduction in systemic blood pressure also occurred, however, patients are generally anxious on the day of their operation and more relaxed postoperatively that may have accounted for the observed change. The reduction in IOP and parallel reduction in systemic blood pressure in the cataract group postoperatively meant that OPP remained stable between visits.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This outcome, which has been attributed to a widening of the anterior chamber angle, [5][6][7][8] has positive implications for glaucomatous eyes resulting in a reduced requirement for IOP-lowering medication in at least one study. 4 Hopkins 9 carried out a pilot study investigating ocular haemodynamics in a small group of cataractous eyes and reported a 20-30% decrease in pulsatile ocular blood flow (POBF) compared to normal healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…[73][74][75][76][77] The IOP reduction of combined phaco and ELT (phaco-ELT) is greater than that of either cataract surgery or ELT alone. 65,72 One likely explanation is the deepening of the anterior chamber angle by extraction of the thickened cataractous lens.…”
Section: Excimer Laser Trabeculotomymentioning
confidence: 99%